2016
DOI: 10.1371/journal.pone.0160088
|View full text |Cite
|
Sign up to set email alerts
|

Speaking Clearly for the Blind: Acoustic and Articulatory Correlates of Speaking Conditions in Sighted and Congenitally Blind Speakers

Abstract: Compared to conversational speech, clear speech is produced with longer vowel duration, greater intensity, increased contrasts between vowel categories, and decreased dispersion within vowel categories. Those acoustic correlates are produced by larger movements of the orofacial articulators, including visible (lips) and invisible (tongue) articulators. Thus, clear speech provides the listener with audible and visual cues that are used to increase the overall intelligibility of speech produced by the speaker. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…In another study that compared sighted and blind speakers, we used the paradigm of lip perturbation to investigate the extent to which visual deprivation affects articulatory compensations [ 13 ]. Ultrasound imaging was used to measure tongue shape and position when producing the vowel /u/ before, during, and after the insertion of a lip tube.…”
Section: Introductionmentioning
confidence: 99%
“…In another study that compared sighted and blind speakers, we used the paradigm of lip perturbation to investigate the extent to which visual deprivation affects articulatory compensations [ 13 ]. Ultrasound imaging was used to measure tongue shape and position when producing the vowel /u/ before, during, and after the insertion of a lip tube.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the size of the vowel space, calculated by the average of the Euclidean distances in the mel-transformed formant space, was significantly smaller than that of age-matched sighted speakers. In a follow-up study, speakers were asked to produce vowels in carrier sentences in 2 speaking conditions: clear speech and conversational speech [3]. In the clear speech condition, more weight was given to intelligibility requirements, causing speakers to produce vowels and consonants with longer duration and/or hyperarticulated gestures.…”
Section: Introductionmentioning
confidence: 99%
“…In contexts where perceptual demands are high, speakers are predicted to prefer round variants of /ɔ/, given that the addition of visible lip rounding enhances the contrast with /ɑ/. This prediction is supported by the findings of Ménard et al ( 2016 ), who show that sighted speakers consider how their speech will be perceived both visually and auditorily, and increase the degree of lip rounding for /u/ in clear speech. The integration of visual speech cues may therefore offer an explanation for the finding of Harrington et al ( 2011 ) that British English /u/ has retained its rounding as it has undergone fronting: in acoustic terms, both [y] and [ɨ] should be viable articulations for fronted /u/, but visibly round [y] is predicted to maintain a stronger contrast with /i/.…”
Section: Discussionmentioning
confidence: 74%
“…More recently, a series of studies by Ménard et al ( 2009 , 2013 , 2015 , 2016 ) has demonstrated the importance of audiovisual perception to speech intelligibility through an investigation of differences in the use of visible articulation by sighted and congenitally blind speakers. Ménard et al ( 2009 ), for instance, tested the production and discrimination of vowel contrasts among sighted and blind speakers of Canadian French.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation